The BAT case : putting tech support on the fast track - Lariviere, Martin A. (SAGE Knowledge. Cases., 2007)
The case explains the grown of Bruce Alfred Technologies and how the expansion of the company has put a strain on its customer service departments, lengthening the amount of time customers have to wait before speaking to a technician. The customer service department must consider whether to start a fast track service, whereby customers would pay to guarantee speaking to a technician in one minute or less.